Synthesis, characterization, and catalytic application of hierarchical nano-ZSM-5 zeolite. Issue 50 (10th August 2020) - Jia, Yanming; Shi, Qinghua; Wang, Junwen; Ding, Chuanmin; Zhang, Kan
Abstract : The crystal size and strong acid amounts of ZSM-5 decrease and the mesopores increase with increasing of KH-560. High MTA catalytic performance could be obtained under synergistic effect of proper strong acid amount, smaller crystal size and abundant hierarchical structure. Abstract : Hierarchical nano-ZSM-5 zeolites (Z5- X ) with different grain sizes were synthesized by varying amounts of 3-glycidoxypropyltrimethoxysilane (KH-560) in the hydrothermal synthesis strategy. Moreover, the conventional ZSM-5zeolite(Z5), which was prepared without KH-560, was used as the reference sample. The crystalline phases, morphologies, porous characteristics, Si/Al molar ratios and acidic properties of all fresh catalysts were characterized using the X-ray diffraction (XRD), Fourier transform infrared spectra (FT-IR), scanning electron microscopy (SEM), N2 adsorption–desorption, inductively coupled plasma atomic emission spectroscopy (ICP) and temperature programmed desorption of ammonia (NH3 -TPD) techniques. Results show that the grain size and strong acid amount of zeolite decreased with the increasing amount of KH-560. The micropore surface areas and the corresponding volume of Z5- X changed less compared with Z5. Consequently, the high shape-selectivity of zeolite was preserved well under the addition of KH-560. However, the mesopore surface areas and the corresponding volume increased significantly with the increasing amount of KH-560. Benefiting from the abundant hierarchical structure, the Z5- X catalysts exhibited a larger coke capacity than the Z5 catalyst. The coke depositions of all the deactivated catalysts were characterized by the thermogravimetric technique (TG), and the results are indicative of the decreased average rate of coke deposition with an increasing amount of KH-560, which could result from the gradually reduced strong acid amount and the nano-sized crystallites. The catalytic performance of methanol-to-aromatics (MTA) indicates that the Z5-0.12 catalyst exhibited higher catalytic activity and selectivity of BTX as the reaction was prolonged, which could result from the synergistic effect among the proper strong acid amount, the smaller zeolite grain size, and the abundant hierarchical structure.